El acoso sexual en el entorno laboral desde una perspectiva jurídica-dogmática - López Espinoza, Hazel Virginia (2026)
Sexual harassment at work is a harmful conduct for the correct development of work relationships, it is a generator of toxic environments and it violates fundamental labor rights. In order to provide a better understanding of the subject, the study analyzes sexual harassment in the workplace from a legal and dogmatic perspective, emphasising important aspects such as: typology, legal regulation, implications and mechanisms that contribute to preventing this practice.